Flexible self-control heater and preparation method thereof
By using the combination of the ALN modified PI film, metal layer, and ALN thermal conductivity in a flexible self -controlled heater, the problem of uniformity and heat agglomeration of temperature equity and the improvement of the uniformity and safety of heating effects.
Patent Information
- Application Number
- CN202411491571.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-24
AI Technical Summary
In the existing flexible self-controlled heaters in large-area and irregular geometric heating devices, there are problems such as poor temperature uniformity and inability to deduce heat accumulation in time, resulting in local overheating and safety hazards.
By mixing the ALN particles evenly in the PI matrix, the ALN modified PI film is made, and the metal layer and ALN thermal conductivity are formed in the surface of the film to form an efficient composite thermal conductivity to achieve uniform dispersing and rapid heat transmission of heat.
It effectively avoids the occurrence of local overheating, prevents the accumulation of heat inside the PPTC heating layer, and improves the uniformity and safety of the heating effect.
Smart Images

Figure CN119351948A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of heaters, and in particular relates to a flexible self-control heater and a preparation method thereof. Background Art
[0002] Compared with traditional resistance heaters, self-controlled heaters based on positive temperature coefficient (PTC) thermistor materials have significant advantages. This type of heater has adaptive temperature control capabilities and can control the temperature of the controlled device within the normal working range without any external control equipment. It has the advantages of lightweight, miniaturization, and energy saving.
[0003] Polymeric positive temperature coefficient (PPTC) material is a composite material in which conductive particles are dispersed in a polymer carrier. By selecting a suitable polymer carrier and conductive particles and controlling the mass fraction of the conductive particles, it can be used as a thermistor material for a flexible self-controlled heater. At present, a flexible self-controlled heater based on PPTC thermistor material can be prepared in a variety of ways, such as printing PPTC slurry on a flexible film and then annealing it, or spraying PPTC mother liquid on a flexible film and then annealing it, or directly hot pressing the PPTC thermistor material on a flexible film, etc. However, for a flexible self-controlled heater with a large area and irregular geometric shape, the current inside its heating layer (PPTC layer) is often unevenly distributed. When the device is working, there is often a temperature difference in different areas of the heating layer, which affects the actual heating effect, and may even cause the device to burn out due to local overheating.
[0004] In addition, the base flexible film is one of the indispensable components of the flexible self-controlled heater, which plays the role of carrying the PPTC heating layer, shaping the device and conducting heat. The flexible base films currently used are mostly made of polymer materials, such as polyacrylonitrile and polyimide. Although these materials have good insulation, mechanical strength, flexibility, thermal stability and chemical stability, they generally have the problem of poor thermal conductivity, which makes it impossible to disperse and conduct the heat generated by the heating layer in time, affecting the actual performance of the device and may even bring safety hazards.
[0005] Therefore, there is an urgent need for a flexible self-control heater and a preparation method thereof to solve the deficiencies of the prior art. Summary of the invention
[0006] In view of the above problems, the purpose of the present invention is to provide a flexible self-controlled heater and a preparation method thereof, wherein the preparation method uniformly dopes AlN particles into a PI matrix to obtain an AlN-modified PI film and sequentially forms a metal layer and an AlN thermal conductive layer on the surface of the film, thereby enabling the obtained flexible self-controlled heater to avoid the occurrence of local overheating and effectively prevent heat accumulation inside the PPTC heating layer.
[0007] To achieve the above objectives, the present invention provides a method for preparing a flexible self-control heater in a first aspect, comprising the following steps:
[0008] (1) adding AlN to a first solvent, then sequentially subjecting the mixture to ultrasonic treatment and ultraviolet irradiation treatment, and then removing the first solvent to obtain modified AlN;
[0009] (2) adding the modified AlN to the PI precursor solution and then stirring continuously until a viscous paste is obtained;
[0010] (3) printing the paste on a glass plate and then heating it to obtain an AlN-modified PI film;
[0011] (4) forming a metal layer on the surface of the AlN-modified PI film;
[0012] (5) forming an AlN thermal conductive layer on the surface of the metal layer;
[0013] (6) A PPTC heating layer and a metal electrode are sequentially formed on the surface of the AlN thermal conductive layer to obtain a flexible self-controlled heater.
[0014] In order to solve the disadvantages of poor surface temperature uniformity of existing flexible large-area heating devices and the problem that heat accumulates inside the device and cannot be discharged in time, the present invention first modifies AlN particles to enhance the compatibility and bonding strength between the AlN particles and the subsequent PI matrix; then the modified AlN is added to the PI precursor solution, and the AlN particles are uniformly fixed inside the PI matrix through continuous stirring, printing, and heating treatment to form an AlN modified PI film. Since AlN is an efficient thermal conductor, uniformly dispersing it in the PI film can effectively improve the dispersed conduction of the heat generated by the PPTC heating layer, which further effectively reduces the accumulation of heat inside the PPTC heating layer and also helps to uniformly and efficiently heat the heated object. In addition, the present invention also forms a metal layer and an AlN thermal conductive layer on the surface of the AlN modified PI film in sequence, wherein the metal layer has extremely high thermal conductivity and can rapidly diffuse heat in the horizontal direction to avoid the formation of local hot spots, which reduces the temperature difference between different areas of the heater and effectively prevents the occurrence of local overheating; and the AlN thermal conductive layer further enhances the efficiency of heat transfer to the inside of the PI film; at the same time, the high thermal conductivity and good insulation of the AlN layer make it an ideal interface material, which enables the AlN layer to form a good interface contact with the metal layer and promotes heat transfer in the vertical direction, which effectively reduces the accumulation of heat inside the heating layer, that is, the present invention combines the metal layer with the AlN thermal conductive layer to form an efficient composite heat conduction path, which not only realizes rapid and uniform heat diffusion in the horizontal direction, but also provides an efficient heat conduction channel in the vertical direction. In summary, the preparation method of the present invention obtains an AlN-modified PI film by uniformly doping AlN particles into a PI matrix and sequentially forms a metal layer and an AlN thermal conductive layer on the surface of the film, so that the obtained flexible self-controlled heater can avoid the occurrence of local overheating and effectively prevent heat accumulation inside the PPTC heating layer.
[0015] Furthermore, in step (1) of the present invention, the particle size of aluminum nitride (AlN) is 10 nm to 30 μm.
[0016] Furthermore, step (1) of the present invention also includes ultrasonic treatment with an ultrasonic power of 100 to 1500 W and a frequency of 30 to 120 kHz for 1 to 12 hours.
[0017] Furthermore, step (1) of the present invention further comprises using a wavelength of 250 to 365 nm and an intensity of 10 to 100 mW / cm 2 UV irradiation treatment for 10 to 120 minutes.
[0018] Furthermore, step (1) of the present invention further comprises removing the first solvent by vacuum rotary evaporation and heating drying in sequence.
[0019] Furthermore, step (2) of the present invention further comprises adding the diamine monomer and the dianhydride monomer into the second solvent under the protection of an inert gas, and stirring at room temperature to obtain a PI precursor solution.
[0020] Furthermore, step (4) of the present invention also includes forming a metal layer with a thickness of 5 to 200 nm on the surface of the AlN-modified PI film by a vacuum evaporation method, wherein the metal of the metal layer is selected from at least one of Au, Ag, Al, Ni and Cu.
[0021] Furthermore, step (5) of the present invention further comprises forming an AlN thermal conductive layer with a thickness of 10 to 1000 nm on the surface of the metal layer by a magnetron sputtering method.
[0022] Furthermore, step (6) of the present invention includes forming a PPTC heating layer on the surface of the AlN thermal conductive layer by hot pressing, and forming a metal electrode on the PPTC heating layer by vacuum evaporation.
[0023] Accordingly, the second aspect of the present invention also provides a flexible self-controlling heater prepared by the above-mentioned method for preparing a flexible self-controlling heater. The flexible self-controlling heater can avoid the occurrence of local overheating and effectively prevent heat accumulation inside the PPTC heating layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The present invention is a schematic diagram of the structure of a flexible self-controlling heater produced by the method for producing a flexible self-controlling heater of the present invention.
[0025] Figure 2 This is a scanning electron microscope image of the AlN thermal conductive layer in the flexible self-controlled heater prepared in Example 1 of the present invention.
[0026] Figure 3 This is a front view of the flexible self-control heater made in Example 1 of the present invention after being cut.
[0027] Figure 4 This is a back view of the flexible self-control heater made in Example 1 of the present invention after being cut. DETAILED DESCRIPTION
[0028] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.
[0029] In order to solve the problems of poor temperature uniformity and possible local overheating in existing flexible self-control heaters with large areas and irregular geometric shapes, the present invention provides a method for preparing a flexible self-control heater, comprising the following steps:
[0030] (1) adding AlN to a first solvent, then sequentially subjecting the mixture to ultrasonic treatment and ultraviolet irradiation treatment, and then removing the first solvent to obtain modified AlN;
[0031] (2) adding the modified AlN to the PI precursor solution and then stirring continuously until a viscous paste is obtained;
[0032] (3) printing the paste on a glass plate and then heating it to obtain an AlN-modified PI film;
[0033] (4) forming a metal layer on the surface of the AlN-modified PI film;
[0034] (5) forming an AlN thermal conductive layer on the surface of the metal layer;
[0035] (6) A PPTC heating layer and a metal electrode are sequentially formed on the surface of the AlN thermal conductive layer to obtain a flexible self-controlled heater.
[0036] Specifically, in step (1) of the present invention, the particle size of aluminum nitride (AlN) is 10 nm to 30 μm. Further, the particle size of aluminum nitride is preferably 10 nm to 1 μm, and more preferably 50 to 100 nm.
[0037] Specifically, step (1) of the present invention further comprises ultrasonic treatment with an ultrasonic power of 100 to 1500 W and a frequency of 30 to 120 kHz for 1 to 12 hours. This allows the AlN powder particles to be uniformly dispersed in the first solvent. For example, the ultrasonic power may be, but is not limited to, 100 W, 300 W, 500 W, 800 W, 1000 W, 1200 W, 1500 W; the ultrasonic frequency may be, but is not limited to, 30 kHz, 50 kHz, 80 kHz, 100 kHz, 120 kHz; and the ultrasonic treatment time may be, but is not limited to, 1 hour, 3 hours, 5 hours, 8 hours, 10 hours, 12 hours.
[0038] Further, the ultrasonic power is preferably 500 to 1200 W, more preferably 800 to 1000 W. Further, the ultrasonic frequency is preferably 60 to 110 kHz, more preferably 80 to 100 kHz. Further, the ultrasonic treatment time is preferably 2 to 8 hours, more preferably 3 to 6 hours.
[0039] Specifically, step (1) of the present invention also includes using a wavelength of 250 to 365 nm and an intensity of 10 to 100 mW / cm 2UV irradiation treatment for 10 to 120 minutes. UV irradiation can oxidize the aluminum nitride surface and increase the surface energy of AlN particles to enhance the compatibility and bonding between AlN particles and the subsequent PI matrix. For example, the wavelength of UV light can be but not limited to 250nm, 300nm, 330nm, 350nm, 365nm; the intensity of UV light can be but not limited to 10mW / cm 2 、30mW / cm 2 、50mW / cm 2 、80mW / cm 2 , 100mW / cm 2 ; The ultraviolet irradiation treatment time can be but is not limited to 10min, 30min, 50min, 70min, 80min, 100min, 110min, 120min.
[0040] Furthermore, the wavelength of the ultraviolet light is preferably 265 to 320 nm, more preferably 265 to 285 nm; the intensity of the ultraviolet light is preferably 30 to 90 mW / cm 2 , more preferably 40 to 80 mW / cm 2 ; The ultraviolet light irradiation time is preferably 10 to 60 minutes, more preferably 20 to 40 minutes.
[0041] Specifically, the first solvent of the present invention is preferably anhydrous ethanol.
[0042] Specifically, step (1) of the present invention further comprises removing the first solvent by vacuum rotary evaporation and heating and drying in sequence. For example, a rotary evaporator familiar in the art can be used to perform vacuum rotary evaporation to remove the first solvent, and a vacuum drying oven can be used to remove the residual first solvent by heating and drying. Furthermore, the heating and drying temperature can be 80 to 250°C, preferably 110 to 210°C, and more preferably 150 to 200°C; the heating and drying time can be 0.5 to 10 hours, preferably 1 to 5 hours, and more preferably 1.5 to 3 hours.
[0043] Specifically, step (2) of the present invention further comprises, under the protection of an inert gas, adding a diamine monomer and a dianhydride monomer to a second solvent, and stirring at room temperature to obtain a PI precursor solution. More specifically, stirring at a stirring rate of 50 to 1000 rpm for 1 to 12 hours at room temperature. Furthermore, the stirring rate is preferably 50 to 300 rpm, more preferably 100 to 200 rpm; the stirring time is preferably 2 to 10 hours, more preferably 4 to 8 hours.
[0044] Further, the diamine monomer of the present invention is at least one of 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, p-phenylenediamine, m-phenylenediamine) and diethyltoluenediamine. The dianhydride monomer is at least one of 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride, 2,2'-biphenyl tetracarboxylic dianhydride, 4,4'-terephthaloyl dipyromellitic dianhydride, phthalic anhydride and 4,4'-(hexafluoroisopropyl) diphthalic anhydride. The second solvent includes at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide and methylamine.
[0045] Further, the molar ratio of the diamine monomer to the dianhydride monomer of the present invention is 2:1 to 1:2, such as but not limited to 2:1, 1:2, 1:1, 1.5:1, 2:1.5. More specifically, the molar ratio of the diamine monomer to the dianhydride monomer is preferably 1.5:1 to 1:1.5, more preferably 1.2:1 to 1:1.2.
[0046] Further, step (2) of the present invention comprises slowly adding the modified AlN to the PI precursor solution under stirring at 50 to 1000 rpm, and then continuously stirring for 0.5 to 12 hours until a viscous paste is obtained. Specifically, the stirring speed is preferably 80 to 300 rpm, more preferably 100 to 200 rpm; the stirring time is preferably 2 to 8 hours, more preferably 3 to 6 hours.
[0047] Furthermore, step (3) of the present invention comprises printing the paste on a glass plate by screen printing or steel plate printing as is well known in the art, and then heating the paste in an oven at 100 to 400° C. for 0.5 to 3 hours to completely imidize the monomer, and cooling the paste to room temperature after heating to obtain an AlN-modified PI film.
[0048] Furthermore, step (4) of the present invention further comprises forming a metal layer with a thickness of 5 to 200 nm on the surface of the AlN modified PI film by a vacuum evaporation method, wherein the metal of the metal layer is selected from at least one of gold (Au), silver (Ag), aluminum (Al), nickel (Ni) and copper (Cu). Specifically, the thickness of the metal layer may be, but is not limited to, 5 nm, 50 nm, 80 nm, 120 nm, 150 nm, 180 nm, and 200 nm. The thickness of the metal layer is preferably 5 to 100 nm, more preferably 10 to 50 nm. More specifically, at 1×10 -6 ~1×10 - 5 Pa vacuum degree Vacuum evaporation is performed at a evaporation rate; the evaporation rate is preferably More preferably
[0049] Furthermore, step (5) of the present invention further comprises forming an AlN thermal conductive layer with a thickness of 10 to 1000 nm on the surface of the metal layer by a magnetron sputtering method. The thickness of the AlN thermal conductive layer may be, but is not limited to, 10 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 800 nm, and 1000 nm; the thickness of the AlN thermal conductive layer is preferably 20 to 200 nm. Specifically, the substrate temperature is room temperature; the background vacuum is 1×10 -6 ~1×10 -3 Pa; the sputtering gas and the reaction gas are argon and nitrogen respectively, and the purity of both is 99.99%; the target material is a metal aluminum target with a purity of 99.999%; the distance from the target material to the substrate is 5 to 10 cm; the overall pressure of the working gas is 0.2 to 5.0 Pa, preferably 0.5 to 3.0 Pa, and more preferably 0.8 to 1.2 Pa; the flow ratio of argon and nitrogen is 8:1 to 1:1, preferably 4:1 to 1:1, and more preferably 2:1 to 1:1; the sputtering power is 200 to 600 W, preferably 200 to 400 W, and more preferably 250 to 350 W.
[0050] Furthermore, step (6) of the present invention includes hot pressing the PPTC slurry onto the surface of the AlN thermal conductive layer to form a PPTC heating layer. Specifically, the PPTC slurry used can be obtained through commercial channels, and the main components include a conductive phase, a polymer carrier, an organic solvent and additives. Specifically, the hot pressing includes hot pressing at a temperature of 100 to 400°C and a pressure of 1 to 50 MPa for 5 to 50 minutes. More specifically, the hot pressing temperature is preferably 150°C to 300°C, more preferably 180 to 250°C; the hot pressing pressure is preferably 3 to 20 MPa, more preferably 5 to 10 MPa; the hot pressing time is preferably 8 to 30 minutes, more preferably 10 to 20 minutes.
[0051] Furthermore, step (6) of the present invention further comprises forming a metal electrode on the PPTC heating layer by a vacuum evaporation method. Specifically, the thickness of the metal electrode is 5 to 200 nm, preferably 20 to 150 nm, and more preferably 50 to 100 nm. More specifically, the metal of the metal electrode includes but is not limited to Au, Ag, Al, Ni or Cu metal. More specifically, the vacuum evaporation method comprises: -6 ~1×10 -5 Pa vacuum degree, the evaporation rate is Preferably More preferably
[0052] Furthermore, the structure of the flexible self-control heater 100 prepared by the method for preparing the flexible self-control heater of the present invention is as follows: Figure 1As shown, the flexible self-controlled heater 100 includes a metal electrode 11, a PPTC heating layer 12, an AlN thermal conductive layer 13, a metal layer 14, and an AlN modified PI film 15 in sequence. When the flexible self-controlled heater 100 provided by the present invention is working, the metal layer 14 has an extremely high thermal conductivity, which can promote the heat generated by the PPTC heating layer 12 to be transferred along the Figure 1 The conduction dispersion in the xy plane direction shown in the figure reduces the temperature difference in different areas of the flexible self-controlled heater 100, effectively preventing the occurrence of local overheating. At the same time, the AlN thermal conductive layer 13 further enhances the efficiency of heat transfer to the inside of the AlN modified PI film 15; at the same time, the high thermal conductivity and good insulation of the AlN thermal conductive layer 13 make it an ideal interface material, which allows the AlN thermal conductive layer 13 to form a good interface contact with the metal layer 14, which improves the heat generated by the PPTC heating layer 12 in the direction perpendicular to the AlN modified PI film 15 (such as Figure 1 The conduction efficiency in the z-axis direction (as shown in the figure) is improved, which effectively reduces the heat accumulation inside the PPTC heating layer 12. In addition, compared with the undoped PI film, the thermal conductivity of the AlN-modified PI film 15 of the present invention is significantly improved, which further improves the dispersed conduction of heat, effectively reduces the heat accumulation inside the PPTC heating layer 12, and helps to heat the heated object uniformly and efficiently, thereby largely solving the disadvantage of poor surface temperature uniformity of existing flexible large-area heating devices, and can overcome the problem that heat accumulates inside the device and cannot be exported in time, so it has reliable safety and good heating effect.
[0053] The purpose, technical scheme and beneficial effects of the present invention will be further described below in conjunction with specific examples. The raw materials used in the examples and comparative examples can all be purchased from the market.
[0054] Example 1
[0055] This embodiment provides a method for preparing a flexible self-control heater, comprising the following steps:
[0056] (1) 1.0 g of AlN powder with a particle size of 50 to 100 nm and 10 ml of anhydrous ethanol are placed in a 25 ml beaker, and then ultrasonic treatment and ultraviolet irradiation treatment are performed in sequence, and then the ethanol is removed to obtain modified AlN; wherein the ultrasonic treatment includes ultrasonic treatment with a power of 1000 W and a frequency of 100 kHz for 3 h, and the ultraviolet irradiation treatment includes ultraviolet irradiation with a wavelength of 280 nm and an intensity of 50 mW / cm 2 The samples were irradiated with ultraviolet light for 30 min to remove ethanol, including first vacuum evaporation using a rotary evaporator and then vacuum drying in a vacuum drying oven at 180°C for 2 h;
[0057] (2) 2 g of 4,4'-diaminodiphenyl ether, 2.2 g of pyromellitic dianhydride (PMDA) and 40 mL of N,N-dimethylacetamide were placed in a 100 ml double-necked round-bottom flask, and stirred at 200 rpm for 6 h at room temperature under argon protection to obtain a PI precursor solution, and then the modified AlN was added to the PI precursor solution at a stirring rate of 200 rpm, and stirred for another 5 h until a viscous paste was obtained;
[0058] (3) printing the paste on a glass plate by screen printing, and then placing it in an oven and heating it according to a heating program to completely imidize the monomer. After heating, cooling it to room temperature to obtain an AlN-modified PI film with a thickness of 85 μm; wherein the heating program is 100°C / 10 min, 150°C / 10 min, 200°C / 10 min, 250°C / 10 min, 300°C / 10 min, 350°C / 10 min, and 400°C / 10 min;
[0059] (4) forming an Au layer with a thickness of 20 nm on the surface of the AlN-modified PI film by vacuum evaporation; wherein the vacuum evaporation conditions include: a vacuum degree of 1×10 -6 Pa, the evaporation rate is
[0060] (5) A 200 nm thick AlN thermal conductive layer is formed on the surface of the Au layer by magnetron sputtering; the magnetron sputtering conditions include: the substrate temperature is room temperature; the background vacuum is 1×10 -5 Pa; the sputtering gas and reaction gas are argon and nitrogen respectively, both with a purity of 99.99%; the target is a metal aluminum target with a purity of 99.999%; the distance from the target to the substrate is 8 cm; the overall pressure of the working gas is 1 Pa; the flow ratio of argon and nitrogen is 2:1; the sputtering power is 300 W;
[0061] (6) The PPTC slurry is hot pressed on the AlN thermal conductive layer to form a PPTC heating layer, and then a 100 nm thick Au electrode is formed on the PPTC heating layer by a vacuum evaporation method to obtain a flexible self-controlled heater; wherein the hot pressing conditions include: a temperature of 200° C., a pressure of 10 MPa, and a time of 10 min; the vacuum evaporation conditions include: a vacuum degree of 1×10 -6 Pa, the evaporation rate is
[0062] Example 2
[0063] The preparation method of the flexible self-controlling heater provided in Example 2 is basically the same as that in Example 1. The difference between the two is only that the thickness of the Au layer formed on the surface of the AlN-modified PI film is different. The thickness of the Au layer in Example 2 is 30 nm.
[0064] Example 3
[0065] The preparation method of the flexible self-controlled heater provided in Example 3 is basically the same as that in Example 1. The difference between the two is only that the thickness of the Au layer formed on the surface of the AlN-modified PI film is different. The thickness of the Au layer in Example 3 is 40 nm.
[0066] Example 4
[0067] The preparation method of the flexible self-controlling heater provided in Example 4 is basically the same as that in Example 1. The difference between the two is only that the thickness of the Au layer formed on the surface of the AlN-modified PI film is different. The thickness of the Au layer in Example 4 is 50 nm.
[0068] Example 5
[0069] The preparation method of the flexible self-control heater provided in Example 5 is basically the same as that in Example 1. The only difference between the two is that the metal material of the metal layer formed on the surface of the AlN-modified PI film is different. The metal layer in Example 5 is an Ag layer.
[0070] Example 6
[0071] The preparation method of the flexible self-control heater provided in Example 6 is basically the same as that in Example 2. The only difference between the two is that the metal material of the metal layer formed on the surface of the AlN-modified PI film is different. The metal layer in Example 6 is an Ag layer.
[0072] Example 7
[0073] The preparation method of the flexible self-controlling heater provided in Example 7 is basically the same as that in Example 3. The only difference between the two is that the metal material of the metal layer formed on the surface of the AlN-modified PI film is different. The metal layer in Example 7 is an Ag layer.
[0074] Example 8
[0075] The preparation method of the flexible self-controlling heater provided in Example 8 is basically the same as that in Example 4. The only difference between the two is that the metal material of the metal layer formed on the surface of the AlN-modified PI film is different. The metal layer in Example 8 is an Ag layer.
[0076] Example 9
[0077] The preparation method of the flexible self-controlling heater provided in Example 9 is basically the same as that in Example 1. The only difference between the two is that the metal material of the metal layer formed on the surface of the AlN-modified PI film is different. The metal layer in Example 9 is an Al layer.
[0078] Example 10
[0079] The preparation method of the flexible self-controlling heater provided in Example 10 is basically the same as that in Example 2. The only difference between the two is that the metal material of the metal layer formed on the surface of the AlN-modified PI film is different. The metal layer in Example 10 is an Al layer.
[0080] Embodiment 11
[0081] The preparation method of the flexible self-controlling heater provided in Example 11 is basically the same as that in Example 3. The only difference between the two is that the metal material of the metal layer formed on the surface of the AlN-modified PI film is different. The metal layer in Example 11 is an Al layer.
[0082] Example 12
[0083] The preparation method of the flexible self-controlled heater provided in Example 12 is basically the same as that in Example 4. The only difference between the two is that the metal material of the metal layer formed on the surface of the AlN-modified PI film is different. The metal layer in Example 12 is an Al layer.
[0084] Embodiment 13
[0085] The preparation method of the flexible self-controlled heater provided in Example 13 is basically the same as that in Example 1. The only difference between the two is the thickness of the AlN thermal conductive layer formed on the surface of the Au layer. The thickness of the AlN thermal conductive layer in Example 13 is 100 nm.
[0086] Embodiment 14
[0087] The preparation method of the flexible self-controlled heater provided in Example 14 is basically the same as that in Example 1. The only difference between the two is the thickness of the AlN thermal conductive layer formed on the surface of the Au layer. The thickness of the AlN thermal conductive layer in Example 14 is 300 nm.
[0088] Embodiment 15
[0089] The preparation method of the flexible self-controlled heater provided in Example 15 is basically the same as that in Example 1. The only difference between the two is the thickness of the AlN thermal conductive layer formed on the surface of the Au layer. The thickness of the AlN thermal conductive layer in Example 15 is 500 nm.
[0090] Example 16
[0091] The preparation method of the flexible self-controlled heater provided in Example 16 is basically the same as that in Example 1. The only difference between the two is the thickness of the AlN thermal conductive layer formed on the surface of the Au layer. The thickness of the AlN thermal conductive layer in Example 16 is 700 nm.
[0092] Embodiment 17
[0093] The preparation method of the flexible self-controlled heater provided in Example 17 is basically the same as that in Example 1. The only difference between the two is the thickness of the AlN thermal conductive layer formed on the surface of the Au layer. The thickness of the AlN thermal conductive layer in Example 17 is 900 nm.
[0094] Comparative Example 1
[0095] Comparative Example 1 provides a method for preparing a flexible self-control heater, comprising the following steps:
[0096] (1) 2 g of 4,4'-diaminodiphenyl ether, 2.2 g of pyromellitic dianhydride (PMDA) and 40 mL of N,N-dimethylacetamide were placed in a 100 ml double-necked round-bottom flask, and stirred at 200 rpm for 6 h at room temperature under argon protection to obtain a PI precursor solution;
[0097] (2) printing the PI precursor solution on a glass plate by screen printing, and then placing it in an oven and heating it according to a heating program to completely imidize the monomer. After the heating is completed, cooling it to room temperature to obtain a PI film with a thickness of 85 μm; wherein the heating program is 100°C / 10min, 150°C / 10min, 200°C / 10min, 250°C / 10min, 300°C / 10min, 350°C / 10min, 400°C / 10min;
[0098] (3) The PPTC slurry is hot pressed on the PI film to form a PPTC heating layer, and then a 100 nm thick Au electrode is formed on the PPTC heating layer by vacuum evaporation to obtain a flexible self-controlled heater; wherein the hot pressing conditions include: temperature of 200°C, pressure of 10 MPa, and time of 10 min; the vacuum evaporation conditions include: vacuum degree of 1×10 -6 Pa, the evaporation rate is
[0099] Comparative Example 2
[0100] Comparative Example 2 provides a method for preparing a flexible self-control heater, comprising the following steps:
[0101] (1) 2 g of 4,4'-diaminodiphenyl ether, 2.2 g of pyromellitic dianhydride (PMDA) and 40 mL of N,N-dimethylacetamide were placed in a 100 ml double-necked round-bottom flask, and stirred at 200 rpm for 6 h at room temperature under argon protection to obtain a PI precursor solution;
[0102] (2) printing the PI precursor solution on a glass plate by screen printing, and then placing it in an oven and heating it according to a heating program to completely imidize the monomer. After the heating is completed, cooling it to room temperature to obtain a PI film with a thickness of 85 μm; wherein the heating program is 100°C / 10min, 150°C / 10min, 200°C / 10min, 250°C / 10min, 300°C / 10min, 350°C / 10min, 400°C / 10min;
[0103] (3) A 20 nm thick Au layer is formed on the surface of the PI film by vacuum evaporation; wherein the vacuum evaporation conditions include: a vacuum degree of 1×10 -6 Pa, the evaporation rate is
[0104] (4) A 200 nm thick AlN thermal conductive layer is formed on the surface of the Au layer by magnetron sputtering; the magnetron sputtering conditions include: the substrate temperature is room temperature; the background vacuum is 1×10 -5 Pa; the sputtering gas and reaction gas are argon and nitrogen respectively, both with a purity of 99.99%; the target is a metal aluminum target with a purity of 99.999%; the distance from the target to the substrate is 8 cm; the overall pressure of the working gas is 1 Pa; the flow ratio of argon and nitrogen is 2:1; the sputtering power is 300 W;
[0105] (5) The PPTC slurry is hot pressed on the AlN thermal conductive layer to form a PPTC heating layer, and then a 100 nm thick Au electrode is formed on the PPTC heating layer by a vacuum evaporation method to obtain a flexible self-controlled heater; wherein the hot pressing conditions include: a temperature of 200° C., a pressure of 10 MPa, and a time of 10 min; the vacuum evaporation conditions include: a vacuum degree of 1×10 -6 Pa, the evaporation rate is Comparative Example 3
[0106] This comparative example provides a method for preparing a flexible self-control heater, comprising the following steps:
[0107] (1) 1.0 g of AlN powder with a particle size of 50 to 100 nm and 10 ml of anhydrous ethanol are placed in a 25 ml beaker, and then ultrasonic treatment and ultraviolet irradiation treatment are performed in sequence, and then the ethanol is removed to obtain modified AlN; wherein the ultrasonic treatment includes ultrasonic treatment with a power of 1000 W and a frequency of 100 kHz for 3 h, and the ultraviolet irradiation treatment includes ultraviolet irradiation with a wavelength of 280 nm and an intensity of 50 mW / cm 2 The samples were irradiated with ultraviolet light for 30 min to remove ethanol, including first vacuum evaporation using a rotary evaporator and then vacuum drying in a vacuum drying oven at 180°C for 2 h;
[0108] (2) 2 g of 4,4'-diaminodiphenyl ether, 2.2 g of pyromellitic dianhydride (PMDA) and 40 mL of N,N-dimethylacetamide were placed in a 100 ml double-necked round-bottom flask, and stirred at 200 rpm for 6 h at room temperature under argon protection to obtain a PI precursor solution, and then the modified AlN was added to the PI precursor solution at a stirring rate of 200 rpm, and stirred for another 5 h until a viscous paste was obtained;
[0109] (3) printing the paste on a glass plate by screen printing, and then placing it in an oven and heating it according to a heating program to completely imidize the monomer. After heating, cooling it to room temperature to obtain an AlN-modified PI film with a thickness of 85 μm; wherein the heating program is 100°C / 10 min, 150°C / 10 min, 200°C / 10 min, 250°C / 10 min, 300°C / 10 min, 350°C / 10 min, and 400°C / 10 min;
[0110] (4) The PPTC slurry is hot pressed on the AlN modified PI film to form a PPTC heating layer, and then a 100 nm thick Au electrode is formed on the PPTC heating layer by vacuum evaporation to obtain a flexible self-controlled heater; wherein the hot pressing conditions include: temperature of 200°C, pressure of 10 MPa, and time of 10 min; the vacuum evaporation conditions include: vacuum degree of 1×10 -6 Pa, the evaporation rate is Comparative Example 4
[0111] This comparative example provides a method for preparing a flexible self-control heater, comprising the following steps:
[0112] (1) 1.0 g of AlN powder with a particle size of 50 to 100 nm and 10 ml of anhydrous ethanol are placed in a 25 ml beaker, and then ultrasonic treatment and ultraviolet irradiation treatment are performed in sequence, and then the ethanol is removed to obtain modified AlN; wherein the ultrasonic treatment includes ultrasonic treatment with a power of 1000 W and a frequency of 100 kHz for 3 h, and the ultraviolet irradiation treatment includes ultraviolet irradiation with a wavelength of 280 nm and an intensity of 50 mW / cm 2 The samples were irradiated with ultraviolet light for 30 min to remove ethanol, including first vacuum evaporation using a rotary evaporator and then vacuum drying in a vacuum drying oven at 180°C for 2 h;
[0113] (2) 2 g of 4,4'-diaminodiphenyl ether, 2.2 g of pyromellitic dianhydride (PMDA) and 40 mL of N,N-dimethylacetamide were placed in a 100 ml double-necked round-bottom flask, and stirred at 200 rpm for 6 h at room temperature under argon protection to obtain a PI precursor solution, and then the modified AlN was added to the PI precursor solution at a stirring rate of 200 rpm, and stirred for another 5 h until a viscous paste was obtained;
[0114] (3) printing the paste on a glass plate by screen printing, and then placing it in an oven and heating it according to a heating program to completely imidize the monomer. After heating, cooling it to room temperature to obtain an AlN-modified PI film with a thickness of 85 μm; wherein the heating program is 100°C / 10 min, 150°C / 10 min, 200°C / 10 min, 250°C / 10 min, 300°C / 10 min, 350°C / 10 min, and 400°C / 10 min;
[0115] (4) A 200 nm thick AlN thermal conductive layer was formed on the AlN modified PI film by magnetron sputtering; the magnetron sputtering conditions included: the substrate temperature was room temperature; the background vacuum was 1×10 -5 Pa; the sputtering gas and reaction gas are argon and nitrogen respectively, both with a purity of 99.99%; the target is a metal aluminum target with a purity of 99.999%; the distance from the target to the substrate is 8 cm; the overall pressure of the working gas is 1 Pa; the flow ratio of argon and nitrogen is 2:1; the sputtering power is 300 W;
[0116] (5) The PPTC slurry is hot pressed on the AlN thermal conductive layer to form a PPTC heating layer, and then a 100 nm thick Au electrode is formed on the PPTC heating layer by a vacuum evaporation method to obtain a flexible self-controlled heater; wherein the hot pressing conditions include: a temperature of 200° C., a pressure of 10 MPa, and a time of 10 min; the vacuum evaporation conditions include: a vacuum degree of 1×10 -6 Pa, the evaporation rate is Comparative Example 5
[0117] This comparative example provides a method for preparing a flexible self-control heater, comprising the following steps:
[0118] (1) 1.0 g of AlN powder with a particle size of 50 to 100 nm and 10 ml of anhydrous ethanol are placed in a 25 ml beaker, and then ultrasonic treatment and ultraviolet irradiation treatment are performed in sequence, and then the ethanol is removed to obtain modified AlN; wherein the ultrasonic treatment includes ultrasonic treatment with a power of 1000 W and a frequency of 100 kHz for 3 h, and the ultraviolet irradiation treatment includes ultraviolet irradiation with a wavelength of 280 nm and an intensity of 50 mW / cm 2The samples were irradiated with ultraviolet light for 30 min to remove ethanol, including first vacuum evaporation using a rotary evaporator and then vacuum drying in a vacuum drying oven at 180°C for 2 h;
[0119] (2) 2 g of 4,4'-diaminodiphenyl ether, 2.2 g of pyromellitic dianhydride (PMDA) and 40 mL of N,N-dimethylacetamide were placed in a 100 ml double-necked round-bottom flask, and stirred at 200 rpm for 6 h at room temperature under argon protection to obtain a PI precursor solution, and then the modified AlN was added to the PI precursor solution at a stirring rate of 200 rpm, and stirred for another 5 h until a viscous paste was obtained;
[0120] (3) printing the paste on a glass plate by screen printing, and then placing it in an oven and heating it according to a heating program to completely imidize the monomer. After heating, cooling it to room temperature to obtain an AlN-modified PI film with a thickness of 85 μm; wherein the heating program is 100°C / 10 min, 150°C / 10 min, 200°C / 10 min, 250°C / 10 min, 300°C / 10 min, 350°C / 10 min, and 400°C / 10 min;
[0121] (4) forming an Au layer with a thickness of 20 nm on the surface of the AlN-modified PI film by vacuum evaporation; wherein the vacuum evaporation conditions include: a vacuum degree of 1×10 -6 Pa, the evaporation rate is
[0122] (5) The PPTC slurry is hot pressed on the Au layer to form a PPTC heating layer, and then a 100 nm thick Au electrode is formed on the PPTC heating layer by a vacuum evaporation method to obtain a flexible self-controlled heater; wherein the hot pressing conditions include: a temperature of 200° C., a pressure of 10 MPa, and a time of 10 min; the vacuum evaporation conditions include: a vacuum degree of 1×10 -6 Pa, the evaporation rate is
[0123] Figure 2 FIG. 1 is a scanning electron microscope image of the AlN thermal conductive layer in the flexible self-controlled heater obtained in Example 1 of the present invention. Figure 2 As shown, the surface morphology of the AlN thermal conductive layer is uniform, dense and flat. This morphology can effectively isolate the metal electrode from the metal layer, avoiding a short circuit between the two, and is conducive to the dispersion and conduction of heat.
[0124] The flexible self-controlled heater prepared in Example 1 is cut into Figure 3-4 The flexible self-control heaters prepared in Examples 2 to 17 and Comparative Examples 1 to 5 were also prepared in the same manner as shown in FIG. Figure 3-4Then, a voltage of 24 V was applied to the cut flexible self-control heaters of Examples 1 to 17 and Comparative Examples 1 to 5, and an infrared thermometer was used to test the central area of the heater device (i.e. Figure 4 The time required for the geometric center point of the "5" area to rise to the specified temperature is shown in Table 1.
[0125] When the flexible self-control heater is working stably, an infrared thermometer is used to test the temperature of different areas of the flexible self-control heater (15 cm×15 cm) of Example 1 and Comparative Examples 1 to 5. The temperature measurement position is the corresponding area (i.e. Figure 4 The geometric center points of the areas 1, 2, 3, 4, 5, 6, 7, 8, and 9 are shown in Table 2.
[0126] Table 1
[0127]
[0128]
[0129] Table 2
[0130]
[0131] It can be seen from Tables 1 to 2 that, compared with Comparative Examples 1 to 5, the flexible self-controlling heaters of Examples 1 to 17 have higher thermal conductivity and smaller temperature differences between different regions of the device, which indicates that the preparation method of the present invention can prevent the occurrence of local overheating and effectively prevent heat accumulation inside the PPTC heating layer by uniformly doping AlN particles into the PI matrix to obtain an AlN-modified PI film and sequentially forming a metal layer and an AlN thermal conductive layer on the surface of the film.
[0132] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a flexible self-control heater, characterized in that: The following steps are involved: (1) adding AlN to a first solvent, then sequentially subjecting it to ultrasonic treatment and ultraviolet irradiation treatment, and then removing the first solvent to obtain modified AlN; (2) adding the modified AlN to the PI precursor solution, and then continuously stirring until a viscous paste is obtained; (3) printing the paste on a glass plate and then heating it to obtain an AlN-modified PI film; (4) forming a metal layer on the surface of the AlN-modified PI film; (5) forming an AlN thermal conductive layer on the surface of the metal layer; (6) A PPTC heating layer and a metal electrode are sequentially formed on the surface of the AlN thermal conductive layer to obtain a flexible self-controllable heater.
2. The method for preparing the flexible self-control heater according to claim 1, characterized in that: The particle size of the AlN in step (1) is 10 nm to 30 μm.
3. The method for preparing the flexible self-control heater according to claim 1, characterized in that: Step (1) also includes ultrasonic treatment with an ultrasonic power of 100 to 1500 W and a frequency of 30 to 120 kHz for 1 to 12 hours.
4. The method for preparing the flexible self-control heater according to claim 1, characterized in that: Step (1) also includes using a wavelength of 250 to 365 nm and an intensity of 10 to 100 mW / cm 2 UV irradiation treatment for 10 to 120 minutes.
5. The method for preparing the flexible self-control heater according to claim 1, characterized in that: Step (1) also includes removing the first solvent by vacuum rotary evaporation and heating drying in sequence.
6. The method for preparing the flexible self-control heater according to claim 1, characterized in that: Step (2) also includes adding the diamine monomer and the dianhydride monomer into the second solvent under the protection of an inert gas, and stirring at room temperature to obtain the PI precursor solution.
7. The method for preparing the flexible self-control heater according to claim 1, characterized in that: Step (4) also includes forming a metal layer with a thickness of 5 to 200 nm on the surface of the AlN-modified PI film by a vacuum evaporation method, wherein the metal of the metal layer is selected from at least one of Au, Ag, Al, Ni and Cu.
8. The method for preparing the flexible self-control heater according to claim 1, characterized in that: Step (5) also includes forming an AlN thermal conductive layer with a thickness of 10 to 1000 nm on the surface of the metal layer by a magnetron sputtering method.
9. The method for preparing the flexible self-control heater according to claim 1, characterized in that: Step (6) includes forming the PPTC heating layer on the surface of the AlN thermal conductive layer by hot pressing, and forming the metal electrode on the PPTC heating layer by vacuum evaporation.
10. A flexible self-controlled heater, characterized in that: The flexible self-control heater is prepared by the preparation method according to any one of claims 1 to 9.